Beyond clinical trials: social outcomes of structured stakeholder engagement in biomedical HIV prevention trials in China. Issue 12 (1st December 2020) - Liu, Chuncheng; Meyers, Kathrine
Abstract: Stakeholder engagement is increasingly recognised and institutionalised as an essential component of HIV-related biomedical research. However, we know little about stakeholder engagement's social outcomes, such as its influence on the community it engages with, in authoritarian regimes and beyond high-income countries. This study evaluates a multi-site structured stakeholder engagement programme conducted in parallel with two HIV prevention studies among men who have sex with men in China. We conducted a one-month ethnographic study and 41 semi-structured interviews with participants of a structured stakeholder engagement programme in six Chinese cities. We found that the structured stakeholder engagement programme offered community stakeholders additional and flexible funding, networking opportunities, increased clinical research literacy, and strengthened their connections with the community. However, the structured stakeholder programme generated unintended consequences in some cases. It caused community stakeholders to expend their social capital, introduced moral conflicts and created tension between stakeholders' 'community representative' and 'research assistant' identities. Our findings suggest that despite these unintended consequences, structured stakeholder engagement could effectively mitigate negative outcomes generated by such engagement if such programmes are more sensitive and responsive to the broader socio-political structure in which trials are embedded.